A methodology for the selection of industrial robots in food handling. (August 2020) - Bader, Farah; Rahimifard, Shahin
Abstract: As the global population continues to rise and consumer demand for a wider variety of food products increases, food manufacturers are exploring various strategies, methods and tools to change and adapt. Furthermore, restriction in access to low-cost labour and introduction of more stringent legislation are forcing the food industry to update their production processes. Industrial robots, a pillar of Industry 4.0, promises many benefits to the food manufacturing industry, especially in responding to these new challenges. The integration of such automation into food manufacturing has been a slow process in comparison to other manufacturing sectors and has largely been limited to packaging and palletising. This research aims to improve the application of industrial robots within food manufacturing through definition of a methodology for the identification of a flexible automation solution for a specific production requirement. The paper explores the four steps within the Food Industrial Robot Methodology (FIRM), through which users define, classify and identify their foodstuff and automation solution. The application of FIRM is exemplified through an industrial case study to support food manufacturers investigating the potential benefits of utilising industrial robots within their production systems. Highlights: Applications of industrial robot in food industry and their automation prospects reviewed. Proposing a 4-step Food Industrial Robot Methodology for the selection of industrial robots for food processing operations. FIRM includes 8 categories for user review and selection, with a few assisting tools provided. Methodology demonstrated using an example from the meat industry.